The Effectiveness of Podcast on Students’ Listening Skill at SMK Prima Bekasi - Agus Kurniawan (Jejak digital: Jurnal Ilmiah Multidisiplin, 2025)
This study aims to measure the effectiveness of using podcasts as a learning medium to improve students’ listening skills in Grade X of SMK PRIMA Bekasi in the academic year 2024/2025. The research method applied was a quasi-experimental design using a Non-Equivalent Control Group Design. The sample consisted of two classes, namely the experimental class (30 students) taught with podcasts and the control class (30 students) taught using conventional methods. The research instrument was a listening skill test consisting of 30 multiple-choice questions and 10 short-answer questions, administered as both a pre-test and a post-test. The results indicated a significant improvement in the listening skills of the experimental class. The average pre-test score in the experimental class was 57.47, which increased to 78.3 in the post-test, with a gain score of +20.83. In contrast, the control class only improved from 55.37 in the pre-test to 61.63 in the post-test, with a gain score of +6.26. The independent samples t-test showed a significance value (p < 0.05), meaning there was a significant difference between the learning outcomes of students in the experimental class and those in the control class. Therefore, this research concludes that podcasts are proven to be effective in enhancing students’ listening skills. Podcasts provide flexibility, varied topics, and authentic language exposure that help train concentration, enrich vocabulary, and familiarize students with different accents and speaking styles.